2022
DOI: 10.21834/ebpj.v7i21.3690
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Tax Education into Non-Accounting Curriculum: A Malaysian and Indonesian Study

Abstract: This study examines whether Malaysian and Indonesian colleges and universities need to formally include tax education in all fields of study at all tertiary level. Three hundred forty-nine academicians from Malaysia and 127 from Indonesia answered the survey. The finding shows that both countries’ academicians hold comparable views on the need to include tax education as an elective course in all fields of study. Furthermore, the results show that both respondents have a good grasp of three basic tax facts. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Belchova and Sobotovicova also supports that taxpayers completed tax-focused subjects had better understanding than those who had not completed (Belchova & Sobotovicova, 2016).Mohd Yusofet. al furthermore conformed that formal tax education should be implemented at the university level for uplifting tax knowledge level of taxpayers by incorporating Malaysian and Indonesian colleges and universities in the study (Mohd Yusof N. A., Safeei, Chuen, & Novita, 2022).An empirical research by Said reported that there was an increase number in tax knowledge before and after the delivery of the material in the classroom (Said, 2018).…”
Section: Resultsmentioning
confidence: 91%
“…Belchova and Sobotovicova also supports that taxpayers completed tax-focused subjects had better understanding than those who had not completed (Belchova & Sobotovicova, 2016).Mohd Yusofet. al furthermore conformed that formal tax education should be implemented at the university level for uplifting tax knowledge level of taxpayers by incorporating Malaysian and Indonesian colleges and universities in the study (Mohd Yusof N. A., Safeei, Chuen, & Novita, 2022).An empirical research by Said reported that there was an increase number in tax knowledge before and after the delivery of the material in the classroom (Said, 2018).…”
Section: Resultsmentioning
confidence: 91%